Association analysis of transcriptome and quasi-targeted metabolomics reveals the regulation mechanism underlying broiler muscle tissue development at different levels of dietary guanidinoacetic acid - Hong, Jieyun; Raza, Sayed Haidar Abbas; Liu, Mengqian; Li, Mengyuan; Ruan, Jinrui; Jia, Junjing; Ge, Changrong; Cao, Weina (Frontiers in Veterinary Science, 2024)
The development and characteristics of muscle fibers in broilers are critical determinants that influence their growth performance, as well as serve as essential prerequisites for the production of high-quality chicken meat. Guanidinoacetic acid (GAA) is a crucial endogenous substance in animal creatine synthesis, and its utilization as a feed additive has been demonstrated the capabilities to enhance animal performance, optimize muscle yield, and augment carcass quality. The objective of this study was to investigate the regulation and molecular mechanism underlying muscle development in broilers at different levels of GAA via multiple omics analysis. The 90 Cobb broilers, aged 1 day, were randomly allocated into three treatments consisting of five replicates of six chickens each. The control group was provided with a basal diet, while the Normal GAA and High GAA groups received a basal diet supplemented with 1.2 g/kg and 3.6 g/kg of GAA, respectively. After a feeding period of 42 days, the pectoralis muscles were collected for histomorphological observation, transcriptome and metabolomic analysis. The results demonstrated that the addition of 1.2 g/kg GAA in the diet led to an augmentation in muscle fiber diameter and up-regulation of IGF1, IHH, ASB2, and ANKRD2 gene expression. However, a high dose of 3.6 g/kg GAA in the diet potentially reversed the beneficial effects on chicken breast development by excessively activating the TGF-β signaling pathway and reducing nucleotide metabolite content. These findings would provide a theoretical foundation for enhancing the performance and meat quality of broilers by incorporating GAA as a feed additive.